2020
DOI: 10.2989/10220119.2020.1825120
|View full text |Cite
|
Sign up to set email alerts
|

Frequent burning maintained a stable grassland over four decades in the Drakensberg, South Africa

Abstract: The mesic temperate montane grasslands of the Drakensberg, located within the broader Drakensberg Alpine Centre in southern Africa (Carbutt and Edwards 2003), are productive and ancient (Ellery and Mentis 1992; Bredenkamp et al. 2002; Bond and Parr 2010). Covering more than 42 000 km 2 of the upland area in KwaZulu-Natal (KZN), with only >2 500 km 2 in formal protected areas (Carbutt et al 2011), these closed-canopy grasslands were shaped by conditions during the late Miocene, which facilitated the spread of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 74 publications
(79 reference statements)
0
14
0
Order By: Relevance
“…Management objectives aimed at maintaining the stability of montane grasslands therefore need to incorporate their dynamic nature in response to fire [67]. Application of fire at the correct frequency and season is essential for optimising grassland biodiversity and condition, which minimises erosion and sediment losses to maintain a steady supply of clean water and maximise storage of soil organic carbon to mitigate climate change [68,69].…”
Section: Fire Management and Policy That Optimizes Grassland Biodiversity Resilience And Water Productionmentioning
confidence: 99%
See 3 more Smart Citations
“…Management objectives aimed at maintaining the stability of montane grasslands therefore need to incorporate their dynamic nature in response to fire [67]. Application of fire at the correct frequency and season is essential for optimising grassland biodiversity and condition, which minimises erosion and sediment losses to maintain a steady supply of clean water and maximise storage of soil organic carbon to mitigate climate change [68,69].…”
Section: Fire Management and Policy That Optimizes Grassland Biodiversity Resilience And Water Productionmentioning
confidence: 99%
“…To understand these dynamics long-term, the Brotherton Fire Experiment (1981-1992 and 2015-present; South Africa; Figure 2) at Cathedral Peak in the Maloti-Drakensberg was established as a small-scale mesocosm-type fire experiment using 1-, 2-, 5-, and 12year fire-return interval treatments to complement the larger research catchment-scale fire experiment discussed previously [69][70][71]. The experiment is generally sampled biennially, but occasionally on an ad hoc basis [71][72][73].…”
Section: Fire Management and Policy That Optimizes Grassland Biodiversity Resilience And Water Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these threats, Afroalpine grasslands of the DMC remain understudied regarding their response to human influence, with most ecological, paleoecological and floristic research focused on lower-elevation Afromontane grasslands of southern Africa (e.g. Joubert et al, 2017;Lodder et al, 2018;Breman et al, 2019;Morris et al, 2021) and Afroalpine grasslands found in East and Central Africa (e.g. Gehrke & Linder, 2014;Johansson et al, 2018;Lézine et al, 2019;Vidal & Clark, 2020).…”
Section: Introductionmentioning
confidence: 99%